PENGARUH PENGUNGKAPAN SUSTAINABILITY REPORTING TERHADAP NILAI PERUSAHAAN: STUDI EMPIRIS IMPLEMENTASI GRI 2021 di BEI - Susianto, Tony Natayo; Wirakusuma, Made Gede (Jurnal Review Pendidikan dan Pengajaran, 2024)
Firm Value is the level of success of a company as projected in its share price and is considered an important aspect for companies and investors. Firm value is frequently used as a tool to characterize a company's condition, which serves as a guide for investors when they make financial decisions. The aim of this study is to ascertain how business value is impacted by sustainability reporting disclosure. This study employs quantitative approach with secondary data analysis from annual reports, also sustainability reports of non-financial companies listed on the Indonesia Stock Exchange in 2022. The sample determination method employed non-probability sampling method with purposive sampling technique, also 144 observations were gained, this research data analysis technique utilizes multiple linear regression analysis. Research data was gained from annual reports, also company sustainability reports. According to the study analysis's findings, business value as determined by Tobin's Q is unaffected by the disclosure of sustainability reporting. The conclusion of this study is to offer an understanding of the information that the number of CSR (Corporate Social Responsibility) disclosures using the 2021 GRI Standards carried out by companies may not necessarily be successful. increase high firm value. Companies that consistently fulfill sustainability practices do not necessarily have high financial or non-financial performance. In conclusion, this study offer the base for comprehending the implementation of GRI Standards 2021 in disclosing sustainability reporting on firm value as proxied by Tobin's Q on sustainability practices for the future